1984
DOI: 10.1007/bf00262532
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and parameters of new populations of meat-type chickens

Abstract: Sire and dam populations of meat-type chickens were developed at the Animal Research Centre, Ottawa to provide unselected control populations suitable for modern broiler research, estimate genetic parameters of broiler traits, and initiate selection experiments. The populations were synthesized from 16 commercial broiler parent stocks (nine sire and seven dam stocks) during two generations of crossbreeding and one generation of random mating. The estimated genetic contribution per stock to the respective popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 16 publications
6
20
0
Order By: Relevance
“…Similarly, observations by Sabri et al (1991) of genetic differences in feed efficiency were reported to be due to differences in energy requirements for growth for the genetic lines evaluated. Consistent with this rationale of the biological relationship between FCR and BWG were high phenotypic and genetic correlation estimates reported by Chambers et al (1984).…”
Section: Body Weight Gain Feed Consumption and Feed Conversion Ratiosupporting
confidence: 73%
See 1 more Smart Citation
“…Similarly, observations by Sabri et al (1991) of genetic differences in feed efficiency were reported to be due to differences in energy requirements for growth for the genetic lines evaluated. Consistent with this rationale of the biological relationship between FCR and BWG were high phenotypic and genetic correlation estimates reported by Chambers et al (1984).…”
Section: Body Weight Gain Feed Consumption and Feed Conversion Ratiosupporting
confidence: 73%
“…These two traits are commonly used in determining performance of both meat and egg-type birds. Further, these traits with an estimated correlation of +0.52 have been of both biological and economic significance towards genetic improvement through selection of faster growing and high producing birds (Chambers et al, 1984;Leenstra et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Two hundred male broiler chicks, derived from a cross of selected male and female lines (Chambers et al, 1984), were reared to 9 days of age in electrically heated, wire-floored battery brooders where they received a crumbled practical broiler starter diet and fresh water ad libitum. At 1500 h on the 9th day, all feed was removed and chicks were fasted overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Nine 'sire-strain' and seven 'dam-strain' broiler breeding stocks were obtained as 1-dayold chicks from the industry in 1978, and from these, new sire and dam populations were synthesized (Chambers et a/., 1984). The hatch in 1981 represented the first generation of the established synthetic populations.…”
Section: Chickens and Managementmentioning
confidence: 99%